UNVEILING THE IMPACT OF POLITICAL CONNECTIONS ON CASH FLOW IN INDONESIAN FIRMS - Bayu Wijayantini; Noormariana Mohd Din; Mohd Zulkifli Muhammad; Alfi Arif; Mohamad Hazeem Sidik, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
One of the critical resources in business, particularly in Indonesia, is political connections. Political power and corporate entities have a mutualistic symbiotic relationship encapsulated in a particular political cost transaction model. There is an inevitable consequence in the form of financial resource sacrifices to establish and preserve that relationship. According to current standards, cash flow reporting cannot satisfactorily account for this outcome. This study aims to test the premise that political connections positively impact aberrant cash outflow by detecting expenditures that do not fall under the purview of regular corporate operations. Eighty-nine organizations listed on the IDX have their financial reports for the years 2016 through 2020, and this research uses panel data from those reports to do a linear regression analysis. According to this research, a company's extracurricular spending is positively impacted by its political connections, even in finance.